Studies of aerodynamics of supersonic generic round shaped bodies - Wanchai, Jiajan (2014)
The purpose of this thesis is to study the external flow over the spin-stabilized rounds at supersonic speeds which is beyond the nominal flight of typical round bodies. The main work of this thesis can be divided into three parts: aerodynamics study and prediction, aerodynamic performance improvement, and aerodynamic testing. For the aerodynamics study, two different methodologies - semi-empirical method and computational fluid dynamics (CFD) - were employed to predict the aerodynamic behaviors and also used to provide better understanding of the physical flow over generic rounds under both non-spinning and spinning conditions. The validation study showed that these approaches can be used with reasonable accuracy to design the round geometry. For the aerodynamic performance improvement, an optimization technique coupled with CFD was developed to optimize the 155 mm round. This technique is new, simple, and more accurate compared with previous techniques in the literature. Moreover, including the stability analysis and improvement into the optimization cycle was proven to be crucial to ensure that the designed shape is realistic. The optimized body provides up to 15% drag reduction and 46% increase in gyroscopic stability while remaining dynamically stable over the whole range of the operating Mach numbers. In addition to the optimization procedure, to further enhance the aerodynamic performance of the round bodies, boattail juncture contouring technique was investigated using CFD. The generic rounds with juncture contouring demonstrated a further reduction in drag by up to 5.4%, while remain within the allowable range of gyroscopically static and dynamic stability. For the aerodynamic testing, to validate the superior performance of an optimum geometry obtained using the optimization procedure, the new optimum round and the standard 155 mm M549 body were tested in the large-size, high flow quality supersonic wind tunnel under non-spinning conditions. The wind tunnel test successfully demonstrated the accuracy and effectiveness of the optimization procedure.